The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.9790/4200-04218490
|View full text |Cite
|
Sign up to set email alerts
|

NSCT edge Enhancement for SIFT key points extraction

Abstract: International audienceImage registration is a key step for matching or mosaicing two or more images taken at different times, and/or with different sensors, hence the need for automatic methods arises. In this work, we present an efficient registration method based on the Non-Subsampled Contourlet Transform (NSCT) combined with the Scale Invariant Feature transform (SIFT) to extract robust local control points. Because NSCT is a shift-invariant multidirectional transform, it is used to extract edges at both sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The Contourlet Transform (CT) was first presented by Do and Vetteli [26], which is a multi-resolution and multidirectional transform, contours are better exhibited by the Contourlet Transform analogized to divers transforms [27]. Da Cunha et al [28] suggested NSCT, which is the shift invariant model of the CT [29], besides that, in the course of image decomposing and reconstructing, the NSCT abolish down and up samples [30], the Figure 2 shows the NSCT structure.…”
Section: Non-subsampled Contourlet Transformmentioning
confidence: 99%
“…The Contourlet Transform (CT) was first presented by Do and Vetteli [26], which is a multi-resolution and multidirectional transform, contours are better exhibited by the Contourlet Transform analogized to divers transforms [27]. Da Cunha et al [28] suggested NSCT, which is the shift invariant model of the CT [29], besides that, in the course of image decomposing and reconstructing, the NSCT abolish down and up samples [30], the Figure 2 shows the NSCT structure.…”
Section: Non-subsampled Contourlet Transformmentioning
confidence: 99%